1987
DOI: 10.1073/pnas.84.18.6340
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and sequence of complementary DNA encoding human extracellular superoxide dismutase.

Abstract: A complementary DNA (cDNA) clone from a human placenta cDNA library encoding extracellular superoxide dismutase (EC-SOD; superoxide:superoxide oxidoreductase, EC 1.15.1.1) has been isolated and the nucleotide sequence determined. The cDNA has a very high G+C content. EC-SOD is synthesized with a putative 18-amino acid signal peptide, preceding the 222 amino acids in the mature enzyme, indicating that the enzyme is a secretory protein. The first 95 amino acids of the mature enzyme show no sequence homology wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
165
0
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(167 citation statements)
references
References 40 publications
1
165
0
1
Order By: Relevance
“…The nucleotide sequence of human EC-SOD cDNA 002947 in EMBL database) has been reported by Hjalmarsson et al (1987). Based on the sequence, 10 specific oligonucleotide primers were designed for polymerase chain reaction (PCR) and direct sequencing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleotide sequence of human EC-SOD cDNA 002947 in EMBL database) has been reported by Hjalmarsson et al (1987). Based on the sequence, 10 specific oligonucleotide primers were designed for polymerase chain reaction (PCR) and direct sequencing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…is expressed in some organisms (11,12). In all cases, enzyme catalysis involves redox cycling of the manganese or copper ion at the active site.…”
mentioning
confidence: 99%
“…However, some reports have suggested that Cu/ZnSOD may also reside in the nucleus, peroxisomes, and lysosomes. [20][21][22] A third form, ecSOD, 23 is secreted into the extracellular environment.…”
mentioning
confidence: 99%